Enter Sir Alfred, or Hitchcock’s Three Du Mauriers - Jean-Loup Bourget (Revue LISA)
The paper first focuses on the three adaptations by Hitchcock of Daphne Du Maurier’s material, Jamaica Inn (1938-39), Rebecca (1939-40) and The Birds (1962-63). It summarizes the very different circumstances of the films’ production, which help explain why Rebecca is much closer to its novelistic source than the other two and why the writer was happy with Rebecca and dissatisfied with the other two. It then proceeds to a brief examination of the friendly and professional relationship between Hitchcock and Daphne’s father, the stage and occasionally film actor Gerald Du Maurier, and speculates about possible thematic connections between Hitchcock and Daphne’s grandfather George Du Maurier, the illustrator and author of Trilby and Peter Ibbetson. It concludes that the complex network between Hitchcock and three generations of Du Mauriers is evidence of the Hollywood director’s abiding English roots and inspiration.